Saúde é comida no prato : o direito humano à alimentação adequada : estudo sobre o estado do Espírito Santo - Gonçalves, Eduardo Boarato (2024)
The concept of FNS has evolved in a continuous process and has kept pace with historical changes and economic interests. In Brazil, the concept of FNS has also undergone a process of evolution and is currently recognized as the “realization of the right of all to regular and permanent access to quality food, in sufficient quantity, without compromising access to other essential needs, based on health-promoting eating practices that respect cultural diversity and are environmentally, culturally, economically and socially sustainable. Food has been included in the list of social rights since 2006. Although hunger had already been on the rise since 2019, research by the Penssan network carried out between 2020 and 2022 showed at the time that just over 40% of households had full access to food. Moderate or severe food insecurity was present in 30.7% of the households surveyed, and 15.5% of these had experienced hunger. The regression in progress between 2004 and 2013, a period related to mitigating food and nutritional insecurity and hunger in Brazil due to inequality, was due to the breakdown of social investments. Espírito Santo is among the states with the lowest food insecurity rates, with a severe food insecurity rate of only 2.2% of the population. However, according to the IBGE, more than 84,000 people do not have access to food. There are only 4 public food banks in the state; in the private sector, there is Sesc Mesa Brasil, established in 2003. There are no popular restaurants or community kitchens in the state. An analysis of the food and nutritional insecurity of families assisted by institutions referenced by the Sesc Mesa Brasil Espírito Santo Program revealed that only 9% of these families are food secure. The percentage of mild and moderate food insecurity in both was 27%, and that of severe food insecurity was 37%. Adding together the percentages of moderate and severe food insecurity reveals the reality investigated, 64% of people are under the most severe forms of food insecurity